Worldwide burden of liver cancer due to metabolic dysfunction-associated steatohepatitis from 1990 to 2019: insights from the Global Burden of Disease study - Huang, Minshan; Chen, Hang; Wang, Hui; Wang, Xianmei; Wang, Da; Li, Yu; Zhou, Qingqing; Zhang, Dan; Li, Mengwei; Ma, Lanqing (Frontiers in Oncology, 2024)
Introduction: Metabolic dysfunction-associated steatohepatitis (MASH) is increasingly becoming a prevalent cause of hepatocellular carcinoma (HCC). Our study examines the burden of MASHrelated HCC globally, regionally, and nationally, along with associated risk factors from 1990 to 2019, considering variables such as age, sex, and socioeconomic status.Objective: We aimed to report the global, regional, and national burden of liver cancer due to MASH and its attributable risk factors between 1990 and 2019, by age, sex, and sociodemographic index.Methods: Utilizing the Global Burden of Disease 2019 project, we analyzed data on prevalence, mortality, and disability-adjusted life years (DALYs) for liver cancer attributable to MASH across 204 countries. We provided counts and rates per 100,000 population, including 95% uncertainty intervals.Results: In 2019, there were 46.8 thousand cases of MASH-related HCC, leading to 34.7 thousand deaths, and 795.8 thousand DALYs globally. While the prevalence increased by 19.8% since 1990, the death and DALY rates decreased by 5.3% and 15.1%, respectively. The highest prevalence was in high-income Asia Pacific, with the greatest increases observed in Australasia, Central Asia, and highincome North America. Southern Sub-Saharan Africa reported the highest death rate, while the lowest rates were in parts of Latin America, Central Sub-Saharan Africa, and Eastern Europe. DALY rates were highest in Southern Sub-Saharan Africa and lowest in Tropical Latin America.Discussion: The burden of MASH-related HCC is expected to rise slightly over the next decade. This disease, which is not associated with the Socio-Demographic Index (SDI), remains a major public health problem. In addition, the escalating rates of obesity, demographic shifts, and an aging population could position MASH as a leading factor in liver cancer cases, surpassing viral hepatitis. It is imperative, therefore, that the forthcoming years see the implementation of strategic interventions aimed at the early detection and prevention of liver cancer associated with MASH.